2012
DOI: 10.21776/ub.natural-b.2012.001.03.5
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany of Medicinal Plants in Bromo Tengger Tribe Area, Bromo Tengger Semeru National Park

Abstract: Diterima tanggal 8Maret 2012, direvisi tanggal 1April 2012 ABSTRAK Telah dilakukan penelitian tentang etnobotani meliputi inventarisasi jenis dan potensi tanaman obat pada masyarakat Tengger, Taman Nasional Bromo Tengger Semeru (TNBTS). Penelitian bertujuan untuk mendapatkan informasi jenis dan potensi tanaman obat pada masyarakat Tengger di kawasan TNBTS. Metode yang digunakan adalah ethnodirect sampling meliputi wawancara langsung maupun semi struktural terhadap penduduk biasa, pemangku adat dan dukun/tabib.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…This is in agreement with Indriyani et al concerning Ethnobotany of Medicinal Plants in the National Park of Bromo, Tengger, Semeru. (Indriyani et al 2012;Kuspraningrum 2018) reported the statement of the community head, stipulating the use of indigenous plants, e.g., fennel, sempretan, insulin leaf, Dutch eggplant on the basis of empirical experience. Furthermore, fennel leaf, Foeniculum vulgare Mill, is used during cold weather, and also to treat stomach pain, by kneading the leaves and applying to the stomach.…”
Section: The Traditional Knowledge Of the Indigenous People Of Tenggermentioning
confidence: 99%
“…This is in agreement with Indriyani et al concerning Ethnobotany of Medicinal Plants in the National Park of Bromo, Tengger, Semeru. (Indriyani et al 2012;Kuspraningrum 2018) reported the statement of the community head, stipulating the use of indigenous plants, e.g., fennel, sempretan, insulin leaf, Dutch eggplant on the basis of empirical experience. Furthermore, fennel leaf, Foeniculum vulgare Mill, is used during cold weather, and also to treat stomach pain, by kneading the leaves and applying to the stomach.…”
Section: The Traditional Knowledge Of the Indigenous People Of Tenggermentioning
confidence: 99%
“…Menurut Indriyani et al (2012), masyarakat Suku Tengger menggunakan tanaman etnobotani sebagai obat untuk mengobati masalah kesehatan yang bersifat ringan. Masyarakat Suku Tengger sebagian besar pengetahuannya tentang tanaman obat adalah sama, di mana mereka mendapatkan pengetahuan tersebut dari orang tuanya.…”
Section: Hasil Dan Pembahasan Pemetaan Persepsi Masyarakat Tengger Terhadap Peran Etnobotani Peta Persepsiunclassified